Penerapan Sistem Jaminan Halal Produksi Daging Giling - Pratiwi, Heni; Hutabarat, Zuhri Saputra (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Halal is the main requirement for Muslim consumers when consuming food products. The halal guarantee system is a mechanism that must be implemented by producers if they want to apply for halal certification to BPJPH (Halal Product Guarantee Organizing Agency). The problem currently experienced by small and medium businesses in the Angso Duo market is that there is no halal certification from BPJPH. Manshurin 354 Meat Mill is a meat mill production house that grinds chicken and beef. The second partner is Manshurin 354 Meatball Printing, which is a business unit that produces meatball printing. This activity aims to fulfill the assignment for the halal product management course and to find out whether the shop has halal certification or not. The result of this activity is awareness of partner business units to implement a halal guarantee system in their businesses. Suggestions for the sustainability of the program include comprehensive outreach to traders' associations and food product producers regarding the importance of halal certification and collaboration between academics and halal certification institutions regarding the management of halal certificates.